Using analytic hierarchy process to rank takaful companies based on health takaful product / Noor Hafizah Zainal Aznam ... [et al.] - Zainal Aznam, Noor Hafizah; Farhan Zakaria, Shahida; Wan Abu Bakar, Wan Asma'a (2015)
This research is conducted to identify the main factor that influencing people to choose health takaful product and to propose the most appropriate benefits to takaful operators to be more aware the needs of participants. Using the opinions of experts in takaful field among lecturers, the researcher intends to rank the factors based on independent variables; inpatient hospitalization, emergency treatment, out-patient treatment and critical illness. All these four factors were analyzed using Analytical Hierarchy Process (AHP) to gain the weights for each by evaluating the respondents' opinion. Afterward, all the criteria were collected into one group to identify the most crucial criterion in choosing health takaful product. As a result, the position of the takaful companies was ranked based on the weights of criteria and the average obtained from pairwise comparison between takaful operators. This research will help the takaful operator in improvement and development of takaful products especially the health takaful products. Moreover, the takaful operator tends to fulfill the desires of participants in ensuring both parties could get win-win situation.